Optimizing inventory policy to mitigate stockouts during the COVID-19 pandemic: a case study of a pharmacy in Riau, Indonesia - Puspitasari, Fransiska Hernina; Chandra, Wilbert; Kartika Dewa, Parama; Bayu Kurniawan, V Reza (OPSI, 2023)
This paper studies on proposed inventory policy at a well-known pharmacy in Riau Province, Indonesia. Pharmacy X often experiences stockouts, especially during the critical period of the COVID-19 pandemic. These stockouts lead to lost sales. The Q and P inventory models are used to determine the optimal order quantity and order period using several simulation scenarios. Storage capacity and the ability of suppliers to supply drugs are constraints in this study. However, only 7 SKUs that often run out will be examined. The purpose of this paper is to minimize the shortage level of the SKUs using a parameter of shortage costs. After simulation, it was proven there was a decrease in the shortage costs in each SKU compared to the actual state. The reduction reached 23% - 74%.